Teletrabalho em instituições públicas: um estudo de caso no Tribunal de Contas do Estado do Ceará - Almeida, Luciana Barbosa Queiroz de (2018)
Teleworking, the result of new opportunities for work relations, came as a process of taking work to the worker, rather than taking it to work. Studies show that teleworking has brought benefits to companies, teleworkers and society, among them: flexibility of time, time and space; the possibility of employment for the disabled and women; the reduction of costs with transportation, food and clothing; the improvement in the quality of life, increasing opportunities for laser, health and family life; productivity. Considering the relevance of the topic, the present study has the general objective of analyzing the feasibility of teleworking in the Tribunal de Contas do Estado do Ceará (TCE/CE), considering the organizational context, functions and individual characteristics of the servers. This is a research of a qualitative nature, with descriptive objectives. In relation to the media, it is classified as a bibliographic, documentary and field study. In the field research, the strategy adopted was the single case study, using the TCE/CE as the unit of analysis. The results show that the TCE/CE presents characteristics of a decentralized organizational structure, with a management style based on Y theory of behavior, having manuals, standardization and procedures to facilitate the expansion of the level of standardization of the activities performed by its staff, and also with a variable remuneration program directly related to the results of productivity and quality of the servers. Having, therefore, structural and cultural characteristics that make feasible the implantation of teleworking. Regarding the functions (tasks) of the TCE/CE that best adapt to telework, it is concluded that the External Control Analysts and the External Control Technicians - that are in performance of activities in the Secretariat of Information Technology and Secretariat of External Control, perform functions that adapt to telework, having seen the complex nature of the low need for continuous communication, the personal knowledge of the server for procedural instruction, the ease in the evaluation and measurement of results and the use of information and communication technologies for the execution of the tasks. Finally, it was also concluded that the servers filled in the functions that best fit the telework in the TCE/CE present profile characteristics suitable for teleworking.